History, Economy and Religion : Mainland Southeast Asia (c. First Century CE-Fourteenth Century CE) - Prasad, Birendra Nath, (Brill | Manohar Publishers & Distributors, 2024)
This book probes two broad themes: socio-economic and cultural ramifications of trade between India and Mainland Southeast Asia; and the processes behind the localisation of Indian religio-cultural influences in Southeast Asia. The areas covered in the book stretch from the Yunnan area of China in the north to the southernmost borders of Thailand in the south, and the Andaman Sea coast of Thailand in the west to the eastern coast of Vietnam in the east.